Pengaruh Net Operating Working Capital Terhadap Firm’s Value di Indonesia [The Effect of Net Operating Working Capital to the Firm's Value in Indonesia] - Stefanie Kole (Jurnal Finansial dan Perbankan (JFP), 2022)
The purpose of this study is to understand the effect of net operating working capital to the value of firms in Indonesia. This study also examines whether the effect is positive or negative. The data is 3,166 observations consisting of 427 listed firms in Indonesia Stock Exchange from 2010 to 2019 with certain criterias. The model used in this study is Fixed Effect Model. The result shows that net operating working capital does not have significant effect to the value of firms. The effectivity of investment management on net operating working capital is an important factor to determine the optimality of the use of net operating working capital.BAHASA INDONESIA ABSTRACTTujuan dari penelitian ini adalah untuk mengetahui pengaruh dari net operating working capital terhadap nilai perusahaan yang terdapat di Indonesia. Penelitian ini juga ingin melihat apakah pengaruh tersebut bersifat positif ataukah negatif. Penelitian ini memiliki 3.166 obeservasi yang terdiri dari 427 perusahaan yang terdaftar di Bursa Efek Indonesia sejak tahun 2010 hingga 2019 dengan beberapa kriteria tertentu. Model yang digunakan dalam penelitian ini adalah Fixed Effect Model. Hasil dari penelitian ini membuktikan bahwa net operating working capital tidak memiliki pengaruh yang signifikan terhadap nilai perusahaan. Efektifitas dari pengelolaan investasi pada net operating working capital penting untuk menentukan optimalitas dari penggunaan net operating working capital.